Including a wind energy conversion system model in electromagnetic transients program - Reis, Francisco A.G.S (2013)
Due to the increasing penetration of wind energy, it is necessary to posses design tools that are able to simulate the impact of these installation in distribution grids. Electromagnetic transients programs are suited to deal with these problems, but a detailed wind energy converter model which is able to carry the transient behaviour of this system is also required. In this paper, an interface between two available software package, EMTP and INDUSAT, containing the digital implementation of these features, is presented. This tool will enable the assessment of the influence that both voltage flickering and power oscillations may have in the performance of distribution networks in face of dispersed wind production. A simple case-study is discussed and the main conclusions are commented.